2010
DOI: 10.1242/dmm.006239
|View full text |Cite
|
Sign up to set email alerts
|

Standard operating procedures for describing and performing metabolic tests of glucose homeostasis in mice

Abstract: The Mouse Metabolic Phenotyping Center (MMPC) Consortium was established to address the need to characterize the growing number of mouse models of metabolic diseases, particularly diabetes and obesity. A goal of the MMPC Consortium is to propose standard methods for assessing metabolic phenotypes in mice. In this article, we discuss issues pertaining to the design and performance of various tests of glucose metabolism. We also propose guidelines for the description of methods, presentation of data and interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
607
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 628 publications
(631 citation statements)
references
References 60 publications
18
607
0
6
Order By: Relevance
“…However, it was not possible to obtain insulin-specific responses using the current experimental protocol, and indeed this is not trivial to achieve in different areas of the CNS. Interestingly, others have found that measurement of muscle (but not liver) insulin sensitivity varies with length of fasting before assessment [49], therefore it is conceivable that shorter periods of fasting could uncover differences in basal signalling, although we did maintain differences in fasting insulin during the 14 h fast. Taken together, our data argue against the development of major changes in basal insulin signalling pathways in the brain in response to HF feeding, and supports a CNS mechanism that is independent of insulin sensitivity underlying the loss of behavioural flexibility in the HF-fed animals.…”
Section: Discussionmentioning
confidence: 72%
“…However, it was not possible to obtain insulin-specific responses using the current experimental protocol, and indeed this is not trivial to achieve in different areas of the CNS. Interestingly, others have found that measurement of muscle (but not liver) insulin sensitivity varies with length of fasting before assessment [49], therefore it is conceivable that shorter periods of fasting could uncover differences in basal signalling, although we did maintain differences in fasting insulin during the 14 h fast. Taken together, our data argue against the development of major changes in basal insulin signalling pathways in the brain in response to HF feeding, and supports a CNS mechanism that is independent of insulin sensitivity underlying the loss of behavioural flexibility in the HF-fed animals.…”
Section: Discussionmentioning
confidence: 72%
“…To test the efficacy of the liposome‐treated scaffold as transplantation site for islets, 800 rat islets were implanted in scaffolds treated with liposomes loaded with 0.5 and 1.0 μg growth factor and compared with untreated controls. Nonfasting blood glucose levels of the mice were monitored three times a week and 2 weeks after transplantation an intraperitoneal glucose tolerance test (IPGTT) was performed 29. Islet function was monitored for 75 days after islet transplantation.…”
Section: Methodsmentioning
confidence: 99%
“…glucose tolerance test was performed following 8 weeks of HF diet feeding, as described previously. 24 In brief, mice were fasted overnight for 16 hours. The test was performed in a quiet room, preheated to +30°C.…”
Section: Glucose Curvementioning
confidence: 99%